A Meta-Analysis Review of The Influence of Digital Technology on The Learning Outcomes of civil engineering students - Santosa, Tomi Apra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to comprehensively examine the influence of the use of digital technology on student learning outcomes in the Civil Engineering study program through a meta-analysis approach. Digital technologies, such as e-learning, software-based simulations, and online collaborative platforms, have become an integral part of the learning process in the Industrial Revolution 4.0 era. However, its effectiveness in improving the learning outcomes of Civil Engineering students still shows mixed findings. The study collects and analyzes quantitative data from a wide range of relevant empirical research, published in the span of the last ten years. The results of the meta-analysis of 13 studies showed that overall, digital technology had a positive and significant influence on the learning outcomes of Civil Engineering students (g = 1.142; p < 0.001) in the high effect size category. These findings provide important implications for the development of technology-based learning strategies in higher education, especially in improving the competencies of Civil Engineering students effectively and adaptively.